UTILIZATION OF BIO, ORGANIC AND INORGANIC FERTILIZER FOR INCREASING FERTILIZER EFFICIENCY AND PRODUCTIVITY OF RICE ON THREE CULTIVICATION SYSTEMS OF LOWLAND RICE - - Surono; Edi Santosa; Erny Yuniarti (Pusbindiklat - LIPI, 2012)
Some rice cultivation systems with integrated nutrient and environmental friendly management have been developed i.e. System of Rice Intensification (SRI) and Integrated Plant Management (IPM). Utilization of bio, organic, and inorganic fertilizer which give more advantages for productivity of lowland need be assessed on various agricultural lands with various rice cultivation systems. Utilization of bio-fertilizer accompanied by addition of compost 2.5 t/ha and inorganic fertilizer ½ (NPK)-recommendation are better to rice growth and yield than addition of compost 5 ton/ha on PTT system and fertilization with NPK-recommendation on farmer customs system. Effect of utilization of bio-fertilizer accompanied by addition of compost 2.5 t/ha and inorganic fertilizer ½ (NPK)-recommendation on farmer customs system, is better in the biological soil characteristics compared to the utilization of compost 5 t/ha or NPK fertilizer recommendation.